Analysis of chromatin changes associated with the expression of globin and non-globin genes in cell hybrids between erythroid and other cells. - Affara, N (1985)
Red blood cell differentiation involves the coordinate expression of a set of polypeptides some of which are erythroid-specific (the abundant globins as well as minor species such as glycophorin, carbonic anhydrase I and the RBC lipoxygenase) whereas others are found also in a subset of other cells, e.g. beta spectrin and a 19 kd polypeptide (ep 19) found in adult liver and kidney as well as erythroid cells. To investigate the genetic mechanisms involved in the regulation of these classes of genes, the expression of lipoxygenase, ep 19 and beta globin mRNAs was investigated in cell hybrids between mouse erythroid (Friend) cells and mouse T-lymphoma or neuroblastoma cells. All three mRNAs are expressed or repressed together in cell hybrids between the Friend cell and lymphoma or neuroblastoma cells respectively. Moreover, studies of the chromatin structure surrounding the genes reveal that erythroid cell-specific DNaseI hypersensitive sites within the ep 19 and beta major globin genes are lost in the Friend cell X neuroblastoma hybrids whereas they are retained in the Friend cell X lymphoma cell hybrids. This implies that the trans-acting mechanism responsible for regulating the RBC phenotype in these cell hybrids acts at the level of the early chromatin changes thought to reflect a pre-activation stage in gene expression.